2022
DOI: 10.3389/fped.2021.704545
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Acute Respiratory Infections in Children Between 0 and 23 Months of Age in a Peri-Urban District in Pakistan: A Matched Case–Control Study

Abstract: Background: Acute respiratory infection (ARI) accounts for nearly 15% of all childhood mortality in South Asia, with children from rural areas at higher risk due to inaccessibility to healthcare facilities. We therefore aimed to identify risk factors associated with ARI in children under 2 years of age in rural Pakistan.Methods: A retrospective 1:2 matched case–control study was conducted between October and December 2018 in Taluka Kotri, Jamshoro District of Pakistan. Cases were identified as children between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…They account for 6% of the global disease burden, which is greater than the burden of diarrheal illnesses and malaria combined [4][5][6]. Globally, ARIs are responsible for 12 million morbidities and 1.3 million fatalities in children under the age of five [7,8], with three-fourths occurring in Sub-Saharan Africa (SSA) [9][10][11][12][13][14][15][16][17][18]. ARIs are responsible for the huge burden of infant and under-five mortality in rural areas [19].…”
Section: Introductionmentioning
confidence: 99%
“…They account for 6% of the global disease burden, which is greater than the burden of diarrheal illnesses and malaria combined [4][5][6]. Globally, ARIs are responsible for 12 million morbidities and 1.3 million fatalities in children under the age of five [7,8], with three-fourths occurring in Sub-Saharan Africa (SSA) [9][10][11][12][13][14][15][16][17][18]. ARIs are responsible for the huge burden of infant and under-five mortality in rural areas [19].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 17 articles examined the relationship between ARI/acute lower respiratory infections and EBF, of which the majority of the articles noted a decrease in ARI in the EBF group ( n = 13) [ 13 , 14 , 24 , 36 , 46 , 53 , 55 , 59 , 63 , 69 , 73 , 74 ]. A total of three papers found no significant relationship between EBF and ARI [ 50 , 68 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acute lower respiratory tract infections (ALRIs) and diarrhea are the major causes of morbidity and mortality among children under 5 years ( 40 ). A study conducted among infants aged 0–23 months in Pakistan reported children comorbid with diarrhea to have higher odds of ARI ( 41 ). A quantitative analysis among Nepali and Indian children found the incidence of ARI to increase when an episode of diarrhea occurred within 28 days before the onset of ARI ( 40 ).…”
Section: Discussionmentioning
confidence: 99%